2000
DOI: 10.1002/1521-4141(200012)30:12<3707::aid-immu3707>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Induction, binding specificity and function of human ICOS

Abstract: Recently, we have identified the inducible co‐stimulator (ICOS), an activation‐dependent, T cell‐specific cell surface molecule related to CD28 and CTLA‐4. Detailed analysis of human ICOS presented here shows that it is a 55‐60‐kDa homodimer with differently N‐glycosylated subunits of 27 and 29 kDa. ICOS requires both phorbol 12‐myristate 13‐acetate and ionomycin for full induction, and is sensitive to Cyclosporin A. ICOS is up‐regulated early on all T cells, including the CD28– subset, and continues to be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
0
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 29 publications
12
114
0
5
Order By: Relevance
“…ICOS costimulation regulates production of multiple cytokines, including IL-4, IL-10, and IFN-␥ (1,4,10,11), and is critical in Ab responses to T-dependent Ags (11)(12)(13)(14)(15). ICOS costimulation regulates effector functions of both Th2 and Th1 cells (16), as well as CD8 ϩ T cells (17,18).…”
Section: Icos-inducedmentioning
confidence: 99%
“…ICOS costimulation regulates production of multiple cytokines, including IL-4, IL-10, and IFN-␥ (1,4,10,11), and is critical in Ab responses to T-dependent Ags (11)(12)(13)(14)(15). ICOS costimulation regulates effector functions of both Th2 and Th1 cells (16), as well as CD8 ϩ T cells (17,18).…”
Section: Icos-inducedmentioning
confidence: 99%
“…8 and 9). Instead, ICOS-L binds to ICOS, a T cell-specific costimulatory molecule homologous to CD28 and CTLA-4 (8)(9)(10). The strong impact of ICOS͞ICOS-L interaction on T cell-mediated immune responses in vivo became evident by the disruption of the ICOS gene in mice.…”
Section: Nducible Costimulator-ligand (Icos-l) Is a Member Of The B7mentioning
confidence: 99%
“…It has been suggested that stimulation of ICOS on CD4 ϩ T cells preferentially promotes IL-10 production (23,32,33). Moreover, the importance of the ICOS molecule in IL-10-producing Tr cells was reported in respiratory tolerance (25).…”
Section: Icos Expression Is Highly Correlated With Il-10 Production Imentioning
confidence: 99%